Analisis Kontribusi Sektor Pariwisata Provinsi Lampung Terhadap Pertumbuhan Pendapatan Nasional Indonesia - Kaisa Zahwa Azhara; Nabila Destia Leviana; Nahdia Hulwa Imania; Dwi Arya Pangestu; M. Yusuf Bahtiar (Tamasya : Jurnal Pariwisata Indonesia, 2026)
This study aims to analyze the contribution and potential of the Lampung Province tourism sector to national economic growth in the 2020-2025 period. Using a quantitative descriptive approach using the Location Quotient (LQ) and Shift Share methods, this study processes secondary data on Gross Regional Domestic Product (GRDP) at constant prices from the Central Statistics Agency. The analysis shows that although Lampung's macroeconomic performance is still dominated by the primary sector, the tourism sector, particularly the accommodation and food and beverage subsector, has demonstrated post-pandemic resilience with a significant positive growth trend. In 2024, the GRDP value of this subsector at the provincial level reached IDR 4,616.76 billion, with strategic areas such as Bandar Lampung City confirming the accommodation sector as a base sector (LQ > 1) with a high competitive advantage. The integration of a creative economy based on local wisdom, such as the use of Tapis cloth and digital marketing, has been proven to increase the attractiveness of destinations, capable of driving the volume of domestic tourist trips to reach 17.87 million trips by 2024. This finding confirms that Lampung's tourism sector is not only a regional economic driver, but also makes a substantial contribution to national income through a multiplier effect on job creation and increasing domestic foreign exchange. Optimizing collaboration between policymakers and accelerating infrastructure development are key to strengthening the strategic position of Lampung tourism in the future.